Fake it for me eaudiobook - Parker, Weston (Bad Boy Greeks, 2020)
I need a woman to help me shut up my big Greek family. And my new intern is perfect for the job, though pretending to have a relationship with her might be a little taboo. Good thing I'm in charge. Being a self-made billionaire, I haven't spent much time looking for love. None actually. Lucky for me, it's fallen right into my lap. This pretty American girl has zero sense of direction, but a good heart and a sexy smile. I've always been smitten by a woman that needs rescuing, or so it seems. Something tells me that she might be more than I bargained for. Either way, I just need her to fake it for me until it appears real. Funny how real it quickly becomes. Contains mature themes.